2022
DOI: 10.1097/cin.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Use of Animation and Gamification in Online Distance Education During Pandemic

Abstract: The study aimed to determine the effects on knowledge and motivation of animation and gamification in online distance education for a diabetes nursing course. This study was a randomized, controlled, prospective study implemented with 70 nursing students. The animation and gamification were applied to the experimental group. Data were collected using the “Diabetes Nursing Knowledge Test,” “Instructional Materials Motivation Survey,” and “Opinion Form on Diabetes Education Supported by Digital Instruments.” The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…After gamification, the study group’s motivation levels in all four areas (i.e., relevance, attention, satisfaction, and confidence) were significantly higher than those of the control group. This finding agrees with that of Inangil et al [ 60 ], who reported significantly higher attention, satisfaction, and total motivation score among the nursing students in the gamified group than control group. Other studies by Aşıksoy [ 24 ] and White and Shellenbarger [ 70 ] reported that gamified FCs increase student motivation and that badges guaranteed that students actively participated in classroom activities, made competitive environments in a positive way, enhanced peer relationships and generate formative feedback.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…After gamification, the study group’s motivation levels in all four areas (i.e., relevance, attention, satisfaction, and confidence) were significantly higher than those of the control group. This finding agrees with that of Inangil et al [ 60 ], who reported significantly higher attention, satisfaction, and total motivation score among the nursing students in the gamified group than control group. Other studies by Aşıksoy [ 24 ] and White and Shellenbarger [ 70 ] reported that gamified FCs increase student motivation and that badges guaranteed that students actively participated in classroom activities, made competitive environments in a positive way, enhanced peer relationships and generate formative feedback.…”
Section: Discussionsupporting
confidence: 93%
“…A study by Lai et al [ 56 ] involving medical students reported significant improvements in the knowledge of the students in the gamified group. Also, our findings are consistent with those of [ 60 63 ] who reported a significant improvement in the knowledge level of the gamified group. In contrast, a study by Trevino et al [ 64 ] and Lee et al [ 65 ] reported that educational games had a similar impact on the knowledge level as attending an engaging, didactic lecture.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This student performance outcome was perhaps not surprising. A recent study has shown that students who used animation learning tools were more motivated compared to those in the control group (Inangil et al, 2022) and the level of motivation positively was found to correlate with learning outcomes (Abdel Meguid et al, 2020). While motivation was not assessed in this study, students demonstrated the autonomy to choose the tools and model of delivery that best suited their interests.…”
Section: Discussionmentioning
confidence: 99%
“…During an initial analysis of the literature, a diversity was found in the application of gamification depending on the object of study. Therefore, it is possible to find research involving the application of gamification in health promotion and disease prevention [ 36 , 37 ] in teaching health professionals [ 38 , 39 ], in teaching during the COVID-19 pandemic [ 40 ], and in school learning [ 41 ].…”
Section: Discussionmentioning
confidence: 99%